Aircraft‐based CH4 flux estimates for validation of emissions from an agriculturally dominated area in Switzerland. Issue 8 (16th April 2014) - Hiller, Rebecca V.; Neininger, Bruno; Brunner, Dominik; Gerbig, Christoph; Bretscher, Daniel; Künzle, Thomas; Buchmann, Nina; Eugster, Werner
<x xml:space="preserve">Abstract</x> For regional‐scale investigations of greenhouse gas budgets the spatially explicit information from local emission sources is needed, which then can be compared with flux measurements. Here we present the first validation of a section of a spatially explicit CH4 emission inventory of Switzerland. The validation was done for the agriculturally dominated Reuss Valley using measurements from a low‐flying aircraft (50–500 m above ground level). We distributed national emission estimates to a grid with 500 m cell size using available geostatistical data. Validation flux measurements were obtained using the eddy covariance (EC) technique and the boundary layer budgeting (BLB) approach that only uses the mean concentrations of the same aircraft transects. Inventory estimates for the flux footprint of the aircraft measurements were lowest (median 0.40 μg CH4m−2s−1), and BLB fluxes were highest (1.02 μg CH4m−2s−1) for the Reuss Valley, with EC fluxes in between (0.62 μg CH4m−2s−1). Flux estimates from measurements and inventory are within the same order of magnitude, but measured fluxes were significantly larger than the inventory emission estimates. The differences are larger than the uncertainties associated with storage of manure, temperature dependence of emissions, diurnal cycle of enteric fermentation by cattle, and the limitations of the inventory that only covers ≥90% of all expected methane emissions. From this we deduce that it is not unlikely that the Swiss CH4 emission inventory estimates are too low.